Efforts to Increase Students' Interest in Learning in Class XII MIPA 4 SMA Negeri 3 Makassar Through the Use of Audio Visual Based Teaching Materials - Adriani, Adriani; Nurhayati, Nurhayati; Juhariah, Sitti (Indonesian Journal of Pedagogical and Social Sciences, 2024)
Abstract. This research aims to increase student's interest in studying physics in class XII MIPA 4 SMA Negeri 3 Makassar for the 2023/2024 academic year through audio-visual-based physics teaching materials. This research is classroom action research, with research subjects of 33 students consisting of 14 men and 19 women. The success of this research is determined if students' interest in classical physics lessons is very high. The method for collecting data is a questionnaire about students' learning interests with presentation analysis. The research results showed that interest in studying physics in the pre-cycle was 50% in the low category, 70% in the high category in the first cycle, and 80% in the very high category in the second cycle. Based on these results, students' interest in learning has increased and achieved indicators of success. Keywords: Interest in learning audio-visual teaching materials